Experimental study of pool scrubbing under horizontal gas injection. (15th June 2022) - Jung, Woo Young; Lee, Dong Young; Kang, Ji-Hoon; Ko, Min-Seok; Kim, Beom Kyu; Lee, Jongchan; Lee, Doo Yong; Lee, Byeonghee; Ha, Kwang Soon
Abstract: The particles present in submerged gaseous jet can be scrubbed by the pool scrubbing phenomena. This study experimentally examines the aerosol scrubbing efficiency during horizontal gas injection under globule to jet regime. Fourteen tests are performed with relevant parameters such as Weber number, submergence, carrier gas steam fraction, and injector size. The Weber number was in the range of 7.8 × 10 4 –8.3 × 10 6 and the submergence of the injector was in the range of 500–2100 mm. The maximum carrier gas steam mass fraction was 83.7%. The quantitative aerosol scrubbing efficiencies and effects with each parameter are compared and examined. The aerosol scrubbing efficiency increased with an increase in Weber number, injector submergence, and carrier gas steam fraction. On the other hand, the aerosol scrubbing efficiency increased with a decrease in injector size under the similar Weber number condition. The measured aerosol scrubbing efficiency (DF) was in the range of 4 –57.3.